Perbedaan Peningkatan Berat Badan Bayi antara Ibu yang Mengkonsumsi Teh Daun Bangun-Bangun (Coleus amboinicus Lour) dan Teh Daun Katuk (Saoropus androgynous) - Trisna Yuni Handayani; Mona Rahayu Putri (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Breast milk is a complete nutrient content that is needed for the growth and development of children. The quality and quantity of breast milk depends on several factors, one of which is the food consumed. Efforts to improve the quality and quantity of breast milk are done both traditionally and modernly, one of which is by consuming the leaves and katuk leaves that have been packaged more practically in the form of tea so as to facilitate nursing mothers in consuming it. This study aims to find out if there is a difference in baby weight gain between mothers who consume wake-up leaf tea (Coleus amboinicus Lour) and mothers who consume katuk leaf tea (Saoropus androgynus). The study used quasi-experimental methods of both groups given different treatments. Comparison of values in both groups to determine the comparison of infant weight gain. The sample count in this study was 30 respondents divided into two groups that were adjusted to the inclusion criteria. Analyze the data using independent sample t-test. The results of the study that there was no significant difference in infant weight gain between mothers who consumed wake-up leaf tea and mothers who consumed katuk leaf tea with a p-value of 0.061. Conclusion Tea Leaves Wake-Up (Coleus amboinicus Lour) and Katuk Leaf Tea (Saoropus androgynus) can increase the weight of the baby.